2012
DOI: 10.3897/zookeys.229.3580
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Osteocephalus buckleyi species complex (Anura, Hylidae) from Ecuador and Peru

Abstract: We present a new phylogeny, based on DNA sequences of mitochondrial and nuclear genes, for frogs of the genus Osteocephalus with emphasis in the Osteocephalus buckleyi species complex. Genetic, morphologic, and advertisement call data are combined to define species boundaries and describe new species. The phylogeny shows strong support for: (1) a basal position of Osteocephalus taurinus + Osteocephalus oophagus, (2) a clade containing phytotelmata breeding species, and (3) a clade that corresponds to the Osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 45 publications
11
51
0
1
Order By: Relevance
“…g . [2, 5, 36, 69]), our results show that the knowledge of the species diversity of Amazonian frogs is highly inadequate. The underestimation of Amazonian species of Scinax (30%) is similar to the percentage of unnamed amphibian species proposed by [70] for the whole Neotropics (39%).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…g . [2, 5, 36, 69]), our results show that the knowledge of the species diversity of Amazonian frogs is highly inadequate. The underestimation of Amazonian species of Scinax (30%) is similar to the percentage of unnamed amphibian species proposed by [70] for the whole Neotropics (39%).…”
Section: Discussionmentioning
confidence: 84%
“…However, at a regional scale (PMIR and EBMR), the proportion of unidentified Scinax species is more than twice as high (82%) as the estimates for the Neotropics. The increase in the known Scinax species richness from the PMIR and EBMR (450%) is the highest increase in Amazonian frog diversity ever reported, being greater than estimates proposed in studies involving the genera Engystomops (150–250% [5]), Hypsiboas (200–350% [5]), Osteocephalus (37.5%–300% [3, 69]), and Pristimantis (200% [71]). Despite the cryptic diversity [7, 21] and the complex taxonomic history of several Scinax species, the high proportion of undescribed species found in the region of PMIR and EBMR is mainly due to (1) integration of different lines of evidence in the species identification process, and (2) the fact that the region represents one of the most poorly-studied areas in Brazilian Amazonia [72].…”
Section: Discussionmentioning
confidence: 91%
“…Some studies have shown that sister species tend to segregate along environmental gradients suggesting ecological speciation and niche lability (Arteaga et al 2016; Graham et al 2004; Ron et al 2012). Other studies have shown that sister species tend to be allopatric but with similar environmental niches (Cadena et al 2012; Ortega-Andrade et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the use of genetic characters in amphibian taxonomy has helped to discover a large number of cryptic species through the upper and lower Amazon Basin (e.g., Almendáriz et al 2014; Brown et al 2008; Brown and Twomey 2009; Caminer and Ron 2014; Elmer and Cannatella 2008; Fouquet et al 2015; Moravec et al 2014; Páez-Vacas et al 2010; Rivera-Correa and Orrico 2013; Rojas et al 2015; Rojas et al 2016; Ron et al 2012; Twomey and Brown 2008). The use of genetic characters in combination with morphological and bioacoustic evidence allows unambiguous delimitation of species under the evolutionary species concept (de Queiroz 1998; de Queiroz 2007; Padial et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Jungfer (2010) compared the holotype (supposing it was a female) with other species of Osteocephalus and considered it a member of the O. buckleyi complex. This conclusion was accepted on face value by Ron et al (2012), and (not surprisingly) reiterated by Jungfer et al (2013). The new material here discussed shows that females of O. inframaculatus range from 59.4-65 mm and males from 41.1-48.2 mm, and thus the species is larger than Jungfer (2010) thought.…”
Section: Discussionmentioning
confidence: 69%